Smart-phone based telemedicine: Instant messaging application as a platform for radiographic interpretations of jaw pathologies - Medhini Madi; Mathangi Kumar; Kalyana Chakravarthy Pentapati; Ravindranath Vineetha (Elsevier, 2021)
Objective: To evaluate the reliability of WhatsApp in comparison to the images viewed on a workstation monitor (gold standard) for the identification and interpretation of radiographic images of jaw pathologies. Methods: 150 panoramic radiographs were screened for the assessment of jaw pathologies in the workstation monitor. The radiographs were sent to two observers (Observer A and B) via WhatsApp® Messenger which were viewed independently on smartphones. A structured proforma was prepared to evaluate the radiographs for the presence or absence of various radiographic pathological characteristics. Results: The reliability of WhatsApp for observers A and B concerning various characteristics like vital structures, pathological fractures, periodontal ligament widening, and root resorption indicated almost perfect agreement (0.8-0.97). The Kappa coefficients for WhatsApp for observers A and B for pre-categorized radiographic impressions were 0.95 and 0.97 which indicated almost perfect agreement. Conclusion: WhatsApp based expert teleradiology consultation can be a suitable and effective alternative for radiographic interpretations.